Beberapa pengamatan 'nilai Sastera Islam' terhadap karya Siti Zainon = The study of specifically examines in the "values of Islamic Literature" in Siti Zainon's creative writing - Yaacob, Adli; Toklubok, Afifah (Global Academic Excellence (M) Sdn Bhd (GAE), 2022)
This study specifically examines the concept of Islamic literature found in the work of Siti Zainon Ismail. Interestingly, Siti Zainon combines painting and literature in her work. The concept of Islamic literature was not founded by Siti Zainon but the author sought to study the application of the concept of Islamic literature that exists in her work. The concepts of Islamic literature that we can find in her work include; first; use of calligraphic elements or Jawi writing, second; the importance of sensitivity to the environment and its society, third; the essence of culture or nation; fourth; no figurativeism; fifth; the use of floral motifs and fauna. These five theories eventually return to the main concept of Islamic Literature in her work, which is to return to the everlasting beauty which is God.